2011
DOI: 10.3851/imp1917
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Intensification with Raltegravir in Subjects with Sustained HIV-1 Viraemia Suppression: A Randomized 48-Week Study

Abstract: Intensification of HAART with raltegravir during 48 weeks was safe and associated with a significant decrease in CD8(+) T-cell activation, and a transient increase of episomal HIV-1 DNA. However, raltegravir did not significantly contribute to changes in CD4(+) T-cell counts, ultrasensitive VL, and total and integrated HIV-1 DNA. These findings suggest that raltegravir impacts residual HIV-1 replication and support new strategies to impair HIV-1 persistence. ClinicalTrials.gov identifier: NCT00554398.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 41 publications
11
99
2
Order By: Relevance
“…Activated CD8 T cells also correlated with HIV 2LTR circles in pTfh cells at entry. These findings are consistent with previous studies of raltegravir intensification in which HIV 2LTR circles were correlated with CD8 T cell immune activation in patients with undetectable plasma HIV RNA levels (50,54). In these studies, however, CD4 T cell activation was not investigated, which may be more important in the context of HIV reservoirs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Activated CD8 T cells also correlated with HIV 2LTR circles in pTfh cells at entry. These findings are consistent with previous studies of raltegravir intensification in which HIV 2LTR circles were correlated with CD8 T cell immune activation in patients with undetectable plasma HIV RNA levels (50,54). In these studies, however, CD4 T cell activation was not investigated, which may be more important in the context of HIV reservoirs.…”
Section: Discussionsupporting
confidence: 82%
“…7A). As the majority of HIV DNA represents defective or mutated non-replicationcompetent virus (48), it is less relevant than 2LTR circles as an indicator of replicating virus (37,38,49,50). The higher frequencies of 2LTR circles in pTfh cells than in non-pTfh cells at week 48 supports the concept that the pTfh cells are more supportive of HIV replication than non-pTfh or total CD4 T CM cells.…”
Section: Discussionsupporting
confidence: 50%
“…The excessive inflammation in HIV-1 infection has been proposed to be associated with persistent but low level viremia as well as with translocation of microbial products, such as LPS, from a compromised gastrointestinal mucosal barrier (30,(45)(46)(47). Since LPS stimulation of TLR4 on monocytes is an important signal for IL-37 production, acting by stabilizing IL-37 mRNA (5), we set out to study this.…”
Section: Discussionmentioning
confidence: 99%
“…2). Initial studies suggested that raltegravir can be used for intensification of ART treatment by reducing viral load further than combinations of other antiretrovirals (31); however, these data are inconsistent (32,33). Raltegravir has been used to treat HIV-infected patients successfully without necessity for boosting with ritonavir, which affords the opportunity for patients to avoid known adverse side effects of PIs.…”
Section: Integrase Inhibitorsmentioning
confidence: 99%